OP56 Hereditary haemochromatosis: genetic iron overload – a missed opportunity for diagnosis and treatment. (26th August 2022) - Atkins, Janice L; Pilling, Luke C; Melzer, David
Abstract : Background: Hereditary haemochromatosis (HH) is a disorder of iron overload and is the most common genetic disorder of northern Europeans. HH is predominantly caused by the HFE p.C282Y genetic variant but also to a lesser extent by the p.H63D genetic variant. The UK has the second highest prevalence of this mutation worldwide, with or 1 in 150 being affected. HH is easily treated with venesection, but many patients are misdiagnosed or diagnosed too late. We examined the diagnosis of HH itself and other associated morbidities by HFE p.C282Y/H63D genotype status in the UK Biobank cohort. Methods: We studied 451, 143 UK Biobank participants of European ancestry, aged 40 to 70 years at baseline. Participants were followed up for a mean of >11 years via hospital inpatient admissions, cancer registry, primary care, and death records. Cox proportional hazard regression tested associations between genotypes (p.C282Y/p.H63D) and risk of incident disease. Analyses were stratified by sex and adjusted for age, assessment centre, genotyping array type and genetic principal components. Results: Participants were a mean age of 56.8 years (SD 8.0) and 54.3% were female. 2, 890 participants were p.C282Y homozygotes (0.6%). At baseline, only 12.1% of male and 3.4% of female p.C282Y homozygotes were diagnosed with HH, increasing to 25.3% and 12.5% respectively by the end of follow-up. Male p.C282Y homozygotes had a substantially increased risk of incident disease including HH, liver disease, arthritis and diabetes compared to those with no mutations. Most notably, p.C282Y homozygous men were at 10.5 times the risk of liver cancer compared to those without the mutation (HR:10.47, 95% CI:6.56–16.69); almost half of the male p.C282Y homozygotes with a liver cancer diagnosis were undiagnosed with HH at baseline. Male p.C282Y homozygotes also had an increased risk of prostate cancer, (HR:1.32, 95% CI: 1.07–1.63) and dementia (HR:1·83; 95% CI:1.23 to 2·72) compared to those without the mutations. Excess morbidity was more modest in homozygote women and in heterozygotes. Conclusion: In this large community genotyped sample, only a small proportion of HFE p.C282Y homozygotes were diagnosed with HH. In males, p.C282Y homozygosity was associated with substantial excess morbidity, and many UK patients are progressing to serious disease before being diagnosed with HH. Since the iron overload associated with p.C282Y homozygosity can be prevented and treated, these findings suggest a missed opportunity for HH diagnosis and treatment. There is a need for expanded case finding, and screening for HH should be considered.